The Concept of Landscape in Geography and the Landscape as Heritage - Risso, Luciene Cristina [UNESP]; DaCunha, F. L.; DosSantos, M.; Rabassa, J. (Springer, 2018)
This chapter aims to present the concept of landscape in Geography through a historical approach. The discussion is handled by the study of the contributions and results from this science area to the debate of cultural landscape embraced as heritage. From this discussion, we argue that Geography can provide a major contribution to the dialogue on heritage issues, not only by concepts but with methodologies which unify Nature and Culture. Thus, we point out the great significance of the geographic concepts for understanding the landscape as a concept and category concerning to heritage.
Keywords: Natural heritage; Landscape; Cultural heritage; Cultural geography